ANALISIS DISIPLIN, KOMUNIKASI DAN KOMPETENSI DAN DAMPAKNYA PADA KINERJA KARYAWAN PADA PKS PT. CILIANDRA PERKASA KABUPATEN KAMPAR - Yusup Yusup; Novia Dwi Pangastikha; Ilyas Ilyas; Sri Hastuti (STIE Bangkinang Publishing, 2020)
Research to determine the effect of discipline, communication and competence on the performance of employees in the PKS PT.Ciliandra Perkasa Kabupaten Kampar Regency. Sampling was carried out by 81 census employees. Data analysis carried uot by multiple linear regression models. Based on the simulthan and parsial test results, the variable of discipline, communication and competence have a significant effect on the performance of employees in the PKS PT.Ciliandra Perkasa Kabupaten Kampar Regency. Contribution of independent variables to the dependent variables is strong equual to 66,30% while the remaining 33,70% is influenced by other variables not examined in this study.